Characterization of the novel HLA‐C*02:207 allele by two next‐generation sequencing methods. (8th November 2021) - Walencik, Alexandre; Calvo De Olmos, Orane; Bonneville, Francoise; Blanchet, Gaelle; Cesbron‐Gautier, Anne
Abstract : The novel HLA‐C*02:207 allele was characterized using two next generation sequencing technologies.